2019
DOI: 10.1111/1365-2745.13218
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of ecosystem aboveground productivity and its process variables under simulated drought stress

Abstract: 1. Projected increases in drought duration and intensity under climate change considerably affect aboveground productivity (ANPP) and associated process variables (photosynthesis rates (P n ), stomatal conductance (g s ), soil respiration (Rs) and soil water content (SWC)).2. Although ANPP has been extensively studied across the ecosystems, there is a little consensus on how the spatiotemporal patterns of ANPP will be altered with increasing drought stress. Here, we present a global meta-analysis of ANPP and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 76 publications
5
41
0
Order By: Relevance
“…Thus, the drought definition is different from region to region. This drought definition could reflect the fact that the water‐deficit stress tolerance of ecosystem has spatial differentiations (Wu et al ., ; Craine et al ., ; Gao et al ., ). Results shown that the spatial distribution of the drought frequency (Figure ) was similar to that of SPEI‐1 drought frequency (Figure ), and has also reflected those detected by the SPEI in other studies (Xu et al ., ; Zhang et al ., ; Um et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the drought definition is different from region to region. This drought definition could reflect the fact that the water‐deficit stress tolerance of ecosystem has spatial differentiations (Wu et al ., ; Craine et al ., ; Gao et al ., ). Results shown that the spatial distribution of the drought frequency (Figure ) was similar to that of SPEI‐1 drought frequency (Figure ), and has also reflected those detected by the SPEI in other studies (Xu et al ., ; Zhang et al ., ; Um et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Contrasting results have also been reported for the effect of drought characteristics. When drought intensity was measured as %PPT, a significant and negative relationship was found, with grassland resistance decreasing as drought intensity increased ( n = 65; Gao, Zhang, Tang, & Wu, ). However, no effect was observed when drought intensity was measured as SPEI ( n = 43; Stuart‐Haëntjens et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Those linear and nonlinear models of ANPP versus MAP have been useful to predict and optimize biomass production over short periods and under near‐normal conditions (Knapp et al, ). However, they may not capture grassland responses to extreme drier conditions (Gao, Zhang, Tang, & Wu, ). Extreme droughts (see Glossary in Table ) may push the system across critical thresholds of productivity (ANPP crit1 ), triggering discontinuous transition from a high‐productivity state to an alternative low‐productivity state (Figure e).…”
Section: Extreme Droughts May Trigger Critical Transitions In Grasslamentioning
confidence: 99%
“…However, they may not capture grassland responses to extreme drier conditions (Gao, Zhang, Tang, & Wu, 2019). Extreme droughts (see Glossary in Table 1) may push the system across critical thresholds of productivity (ANPP crit1 ), triggering discontinuous transition from a high-productivity state to an alternative low-productivity state (Figure 1e).…”
Section: E X Treme Droug Hts May Tri G G Er Critic Al Tr An S Iti Omentioning
confidence: 99%
See 1 more Smart Citation